Induction of the 72 kDa heat shock protein by glucose ingestion in black pregnant women - Jaffe, Shirlee (Springer Netherlands, 2013)
Obese Black women are at increased risk for development of gestational diabetes mellitus and have worse perinatal outcomes than do obese women of other ethnicities. Since hsp72 has been associated with the regulation of obesity-induced insulin resistance, we evaluated associations between glucose ingestion, hsp72 release and insulin production in Black pregnant women. Specifically, the effect of a 50-g glucose challenge test (GCT) on heat shock protein and insulin levels in the circulation 1 h later was evaluated. Hsp27 and hsp60 levels remained unchanged. In contrast, serum levels of hsp72 markedly increased after glucose ingestion (p = 0.0054). Further analysis revealed that this increase was limited to women who were not obese (body mass index <30). Insulin levels pre-GCT were positively correlated with body mass index (p = 0.0189). Median insulin concentrations also increased post GCT in non-obese women but remained almost unchanged in obese women. Post-GCT serum hsp72 concentrations were inversely correlated with post GCT insulin concentrations (p = 0.0111). These observations suggest that glucose intake during gestation in Black women rapidly leads to an elevation in circulating hsp72 only in non-obese Black women. The release of hsp72 may regulate the extent of insulin production in response to a glucose challenge and, thereby, protect the mother and/or fetus from development of hyperglycemia, hyperinsulinemia, and/or immune system alterations.